2021
DOI: 10.1007/s41030-021-00173-6
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Analysis of Treatment Patterns Among Hospitalized Patients with Pulmonary Arterial Hypertension

Abstract: Introduction: Hospitalization is an important clinical factor associated with survival and rehospitalization in patients with pulmonary arterial hypertension (PAH). Thus, this study examined treatment patterns before and after hospitalization in the US-specific population. Methods: Adult PAH patients in the United States were identified using the Optum Ò Clinformatics Ò database from January 1, 2014, to June 30, 2019, and were required to have continuous health plan enrollment for at least 6 months prior to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 34 publications
9
5
0
Order By: Relevance
“…The median age of the patients in this study was similar to that found in some studies in Asia (47.0–50.8 years) 20 , 21 and Europe (49.6–52.0 years), 22 , 23 , 24 but in other reports from Europe (61.0–61.6 years), 13 , 14 , 25 North America (62.7–68.1 years) 17 , 26 , 27 , 28 and Oceania (60.0 years), 29 patients were older, 13 , 14 , 17 , 25 , 26 , 27 , 28 , 29 and there was a predominance of women (82.1% vs. 61.0–79.0%). 13 , 14 , 15 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 Arterial hypertension was the most prevalent comorbidity in this report, which is consistent with the literature. 17 , 20 , 26 , 27 , 28 , 29 , 30 , 31 Pulmonary arterial hypertension (Group 1) was the most prevalent, in line with other studies with real‐world evidence, 20 , 22 , 23 , 25 and most of the patients had WHO Functional Class I; this diffe...…”
Section: Discussionsupporting
confidence: 90%
“…The median age of the patients in this study was similar to that found in some studies in Asia (47.0–50.8 years) 20 , 21 and Europe (49.6–52.0 years), 22 , 23 , 24 but in other reports from Europe (61.0–61.6 years), 13 , 14 , 25 North America (62.7–68.1 years) 17 , 26 , 27 , 28 and Oceania (60.0 years), 29 patients were older, 13 , 14 , 17 , 25 , 26 , 27 , 28 , 29 and there was a predominance of women (82.1% vs. 61.0–79.0%). 13 , 14 , 15 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 Arterial hypertension was the most prevalent comorbidity in this report, which is consistent with the literature. 17 , 20 , 26 , 27 , 28 , 29 , 30 , 31 Pulmonary arterial hypertension (Group 1) was the most prevalent, in line with other studies with real‐world evidence, 20 , 22 , 23 , 25 and most of the patients had WHO Functional Class I; this diffe...…”
Section: Discussionsupporting
confidence: 90%
“…Since combination therapy is costly [23], it is important for healthcare providers and payers to have practical and easy-to-use risk assessment tools to predict the need for possible treatment interventions among patients with PAH. Alongside those of other recent real-world studies [21,22,24], the findings of the current study regarding the high proportions of patients with PAH who experienced hospitalization within 1 year following initiation of at least one PAH indicated medication, with 96% treated with monotherapy from 2009 through 2019, suggest that there remain significant barriers to utilization of combination therapy even among high-risk patients. In a study that examined the transition of care of patients with PAH from hospitalization to the outpatient setting and its improvement describe prior authorization requirements, PAH medication complexity, required enrollment into risk evaluation programs, and specialty pharmacy dispensing as barriers to receiving treatment with PAH indicated medications [25].…”
Section: Discussionsupporting
confidence: 67%
“…On the basis of such favorable clinical trial evidence for combination therapy, it is recommended in the ESC/ERS PH treatment guidelines initially for treatment-naı ¨ve newly diagnosed patients with PAH and those who are already treated [13,20]. Despite the evidence-based 2015 treatment recommendations, the utilization of combination therapy among patients with PAH in the USA has had a slow uptake [21], reaching a reported maximum of approximately 20% in an observational study of 3116 patients with PAH selected from a US administrative commercial claims database between January 2014 and June 2019 [22]. Furthermore, in this study by Ogbomo et al [22] of hospitalized patients with PAH, 65% were treated with monotherapy prior to hospitalization and less than 7% had treatment escalation following an all-cause hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, 47−58% of patients with PAH were reported to be receiving PDE5i, whereas only 6% were receiving riociguat [ 127 , 128 ].…”
Section: Current Status Of Sgc Stimulators and Pde5i In Phmentioning
confidence: 99%